Some Properties of Pythagorean Fuzzy Normed Ideals - Adak, Amal; Gunjan, Manish Kumar (Communications in Mathematics and Applications, 2025)
Pythagorean fuzzy sets are an advanced extension of fuzzy sets, building upon the framework of intuitionistic fuzzy sets and offering a more comprehensive solution to the limitations inherent in intuitionistic fuzzy theory. This study introduces the concept of Pythagorean fuzzy normed ideals (PFNIs). It explores the intrinsic product between two PFNIs, presenting key results related to this operation. Additionally, the study introduces the concept of characteristic functions in the context of PFNIs and discusses several significant properties of these functions. Furthermore, important findings concerning the epimorphism of Pythagorean fuzzy normed ideals are also presented.